The phytochemical and pharmacological actions of Entada africana Guill. & Perr. - Yusuf, A.J. (Heliyon, 2019)
Entada africana (Ea, Asteraceae) has been widely used traditionally to treat different ailments, as food, insecticides, source of gums, in some small carpentry works. Studies on the pharmacognostic characterization, nutritional, elemental and physicochemical contents has been reported. In vivo and in vitro studies on the plant validated some ethnomedicinal claims of the use of the plant as an anti-inflammatory, analgesic, antibacterial, antioxidant, antiviral, anti-angiogenic, cytotoxic agents among others. Triterpenes, saponins, flavonoids and sugars were reported as bioactive constituents which might be responsible for the aforementioned pharmacological actions of the plant. However, more researches are required in order to isolate bioactive compounds from the different parts of Ea and evaluate their effects on different ailments.